Students Teaching Astronomy Related Science (STARS) - Kachur, Reynee; Seidling, Sara; DeVries, Lindsey (Proceedings of the Wisconsin Space Conference, 2012)
The Students Teaching Astronomy Related Science (STARS) program was designed to promote the interest in space-related science to the Oshkosh Area School District Lighted School House (LSH) K-5th grade students. Through a partnership with UW Oshkosh Science Outreach and the LSH, the STARS program provided 60 K-5th graders of the LSH program 12 weeks of hands-on learning experiences dealing with space and aerospace content outside of the regular school day and the normal science curriculum. The astronomy related science curriculum developed for this program utilized activities from UW Oshkosh Science Outreach and NASA, and included two visits to the Buckstaff Planetarium for an age appropriate planetarium show. Results of this project indicate that this program was successful in increasing the knowledge of space-related science, brought science to â€œlifeâ€ for elementary students, and made space and aerospace education exciting and engaging.Â 